EFFECT OF VANILLIN QUALITY ON THE SYNTHESIS AND SOLID DISPERSION SYSTEMS ON PGV-0 ANTIOXIDANT CAPACITY - RAMADHAN, HAFIZ; FORESTRYANA, DYERA; ADISAPUTRA, GUSTI TIRTA; MUHARRAM, SITI RAHMAH (International Journal of Applied Pharmaceutics, 2022)
Objective: Pentagamavunon-0 (PGV-0) was a curcumin analog with antioxidant properties and has been synthesizing with improvement techniques using vanillins with different qualities. PGV-0 has a low bioavailability but could be increased solubility by making a solid dispersion system. This study aimed to determine the antioxidant properties of PGV-0 that were synthesized with different quality starting materials of vanillin and also to obtain the effect of PEG 6000 and maltodextrin solid dispersion systems. Methods: PGV-0 was synthesizing by mixing cyclopentanone into two different groups of vanillins (vanillin pro analysis and vanillin “Kapal Layar”) using an HCl catalyst. The purity of products was identified with TLC (Thin Layer Chromatography) and spectrophotometrically compared with PGV-0 standard. Solid dispersion system consisting of two treatment groups: PEG 6000 and maltodextrin groups. The measurement of antioxidant properties was examined by Cupric Ion Reducing Antioxidant Capacity (CUPRAC). Results: PGV-0 of vanillin pro analysis group (EC50= 13.62 ppm) was found higher antioxidant capacity as compared to the vanillin “Kapal Layar” group (EC50= 15.35 ppm). The solid dispersion system of PGV-0-PEG 6000 at ratio 1:10 has shown powerful antioxidant capacity (EC50= 9.00 ppm) than the PGV-0-PEG 6000 at ratio 1:5 group (EC50= 10.65 ppm). PGV-0-maltodextrin at ratio 1:10 (EC50= 11.96 ppm) also has powerful antioxidant activity when compared with PGV-0-maltodextrin at ratio 1:5 (EC50= 13.63 ppm). Conclusion: The results of the study showed that the use of vanillin with different qualities in PGV-0 synthesis and also solid dispersion systems can affect the antioxidant activity of PGV-0.